Pengelolaan obat di Puskesmas Mandai Kabupaten Maros - hijrah, muh fauzar (Universitas Sulawesi Barat, 2019)
Public health is a part of the government sub-division which focused on the treatment and defrayal of a medication .They’re consists of primary health treatment and secondary health treatment. Those medicines from the local medicine warehouses are distributed to the whole local government clinics every year regularly .The necessities of the medicines are very crucial. Specially when the clinics are out of supplies . The aim of this study is to determine how the medicines management system based on the strategy , procurement, storage, and distribution atMandai clinic Maros regency .This study uses qualitative method by using a phenomenology approach . There are five informants which qualified based on purposive sampling technique . Collection data was done by using depth interview and direct observationat Mandai clinic in Marosregency. From these resultsit can beconclude thatthe procurementand storage ofdrugs in Mandai clinic Maros regency should be referred to theguidelines of the approval managementof drugsas well asmaintaining the planning and distribution of drugs. Keywords: Management, Medicine, Health Center